Study of microstrip-fed slot antennas - Li, Quan. (2008)
Microstrip-fed slot antennas have most of the advantages possessed by microstrip patch antennas, such as, low profile, simple and inexpensive to fabricate using modern printed-circuit technology, compatible with MMIC design, etc.